Is there a gap in economic culture between EU countries and the transition economies? - Zver, Milan (Managing global transitions, 2004)
The process of EU enlargement is in its final stage, the CEECs have more or less adapted to the western standards, which is not yet sufficient for successful completion of the transition process successfully. We have learned from the failed communism that the imported norms, institutions and practices can cause entropy, unless they reflect the prevailing cultural orientation in the society. People should believe that what they are presented as right (norms) is also good (values). For this reason the system of norms and values should be developed simultaneously. The research results show that the symptoms of economic cultures are less evident in the CEECs than in the selected EU countries, thus the democratic socialization (stimulated from outside) is the key issue. For this reason the CEECs should be included in the network of the Euro- Atlantic integrations as soon as possible in order to ensure the democratic stability and economic efficiency of Europe.
Keywords: Central Europe; democracy; demokracija; družbene spremembe; Eastern Europe; ekonomski razvoj; European Union; Evropska unija; integracija; Srednja Evropa; tranzicija; vrednote; Vzhodna Evropa